The evolutionary dynamics of influenza A and B viruses in the tropical city of Managua, Nicaragua - Nelson, Martha I. (2014)
Despite mounting evidence of the high disease burden of influenza in tropical regions, relatively little viral sequence data is available from tropical countries in the Western hemisphere. To understand the evolutionary dynamics of influenza A and B viruses in Managua, Nicaragua, we performed a phylogenetic analysis of 1,956 influenza viruses, including 335 collected for this study during 2007–2010 from a population-based cohort in Managua. North America was consistently identified as the most significant source of influenza virus diversity in Managua, although South America and Mexico were important viral sources during the 2009 A/H1N1 pandemic. The low number of viral introductions of Central American origin may reflect differences in the seasonality of influenza in Nicaragua versus neighboring countries, and underscores the need for additional data in this understudied region.